APLIKASI PEMBELAJARAN KOOPERATIF DALAM KONSEP TRANSPORTASI PADA SISWA KELAS II SLTP NEGERI 1 SURUH KABUPATEN SEMARANG - RIEZKY MAYA PROBOSARI (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2004)
The Objectives of the research was to know the effect of cooperative teaching model to increase the comprehension of digestive concept toward the students in the second grade of SLTP Negeri 1 Suruh Kabupaten Semarang.Descriptive qualitative approach was applied in the research with Collaborative Action Research. Questioner and documentary of daily notes and exercises collect the data. To keep the data valid, observations rechecking by other teacher, instructor or the consultant were carried out. Based on the research with was done, it can be conclude that the application of cooperative teaching model have positive effect to the comprehension of digest concept toward the students. The learning motivation and achievement and the mean of score after treatment were better than before